Moderation Firm Size on Influence Working Capital to Total Asset and Debt to Equity Ratio on Share Prices - Sukirno, Sukirno; Prsetyo, Muhamad Guntur (Universitas Serang Raya, 2023)
Information about ratiosWorking Capital to Total Asset and Debt Equity Ratio when viewed withsignaling theory will provide positive/negative signals to investors so that it will influence share prices. RatioFirmsize based on contingency theory, it is then tried as a moderator to evaluate the strengthening/weakening of the relationship. This research aims to determine the effectWorking Capital to Total Asset and Debt Equity Ratio to Firmsize-moderated Share Prices. The research population was 281 companies listed on the Southeast Asian stock exchange in the 2012-2020 period, then sampled using purposive sampling to obtain 17 sample companies according to the criteria. The data was then analyzed using Moderating Analysis Regression. The research results show. The research results showWorking Capital to Total Asset significant positive effect on stock prices,Debt Equity Ratio significant negative effect on stock prices, firmsize is able to moderate the effectworking capital to total asset on share prices and firm size are also able to moderate the influencedebt equity ratio to the stock price.